Outcomes of low-molecular-weight heparin treatment for venous thromboembolism in patients with primary and metastatic brain tumours - Chai-Adisaksopha, Chatree; Linkins, Lori-Ann; ALKindi, Said Y.; Cheah, Matthew; Crowther, Mark A.; Iorio, Alfonso (Thrombosis and Haemostasis, 2017)
Venous thromboembolism (VTE) is one of the most common complications in patients with brain tumours. There is limited data available in the literature on VTE treatment in these patients. We conducted a matched retrospective cohort study of patients with primary or metastatic brain cancer who were diagnosed with cancer-associated VTE. Patients were selected after a retrospective chart review of consecutive patients who were diagnosed with cancer-associated VTE between January 2010 and January 2014 at the Juravinski Thrombosis Clinic, Hamilton, Canada. Controls were age- and gender-matched patients with cancer-associated VTE from the same cohort, but without known brain tumours. A total of 364 patients with cancer-associated VTE were included (182 with primary or metastatic brain tumours and 182 controls). The median follow-up duration was 6.7 (interquartile range 2.5–15.8) months. The incidence rate of recurrent VTE was 11.0 per 100 patient-years (95 % CI; 6.7–17.9) in patients with brain tumours and 13.5 per 100 patient-years (95 % CI; 9.3–19.7) in non-brain tumour group. The incidence of major bleeding was 8.6 per 100 (95 % CI; 4.8–14.7) patient-years in patients with brain tumours versus 5.0 per 100 patient-years (95 % CI; 2.8–9.2) in controls. Rate of intracranial bleeding was higher in brain tumour patients (4.4 % vs 0 %, p-value=0.004). In summary, rates of recurrent VTE and major bleeding were not significantly different in patients with cancer-associated VTE in the setting of primary or metastatic brain tumours compared those without known brain tumours. However, greater numbers of intracranial bleeds were observed in patients with brain tumours.
Keywords: Anticoagulants; haemorrhage; cancer; low-molecular-weight heparin; venous thrombosis